Australian and New Zealand Anaesthetic Allergy Group/ Australian and New Zealand College of Anaesthetists Perioperative Anaphylaxis Management Guidelines. Issue 2 (March 2017) - Kolawole, H.; Marshall, S. D.; Crilly, H.; Kerridge, R.; Roessler, P.
Anaphylaxis is an uncommon but important cause of serious morbidity and even mortality in the perioperative period. The Australian and New Zealand College of Anaesthetists (ANZCA) with the Australian and New Zealand Anaesthetic Allergy Group (ANZAAG) have developed clinical management guidelines that include six crisis management cards. The content of the guidelines and cards is based on published literature and other international guidelines for the management of anaesthesia-related and non–anaesthesia-related anaphylaxis. The evidence is summarised in the associated background paper (Perioperative Anaphylaxis Management Guidelines [2016]www.anzca.edu.au/resources/endorsed-guidelines andwww.anzaag.com/Mgmt%20Resources.aspx ). These guidelines are intended to apply to anaphylaxis occurring only during the perioperative period. They are not intended to apply to anaphylaxis outside the setting of dedicated monitoring and management by an anaesthetist. In this paper guidelines will be presented along with a brief background to their development.